Management between continuity and change: A case-study from Hungary - Tamás S. Vamosi (Journal for East European Management Studies, 2001)
This study examines how new concepts affect management in a Hungarian, previously government-owned company. The case-study is analysing how the concepts market and market economy are brought into the company and affect management. There is special focus on how management is constituted between cargoes-of-thoughts and a new everyday life of reality. With Berger and Luckmann (1966) as the primary frame of reference the paper will focus on practices in selected parts of management in the case company. It is shown that some parts of management (surprisingly) technically are almost unchanged in the new 'everyday life of reality' despite a new purpose, whereas other parts of management are quite new. In conclusion, the analyses will reveal that postrationalizations and alternations have attributed to rationality . in a struggle against former cargoes-of-thoughts. – – In dieser Untersuchung werden die Auswirkungen neuer Konzepte auf das Management eines ungarischen Unternehmens betrachtet, das früher ein Staatsunternehmen war. Mit Hilfe von Berger/Luckmann (1966) wird untersucht, wie die Konzepte des Marktes und der Marktwirtschaft in das Unternehmen eingeführt werden und das Management beeinflussen. Besondere Betonung liegt auf den Einflüssen, denen das Management aus alten Denkweisen einerseits und einem vollkommen neuen Alltag andererseits ausgesetzt ist. Es wird gezeigt, dass einige - insbesondere technische - Bereiche des Managements kaum Veränderungen aufweisen, obwohl sich die Ziele vollständig gewandelt haben. Andere Managementbereiche sind hingegen recht neu. In der Untersuchung wird gezeigt, dass Veränderungen sowie neue Rationalitäten nicht unabhängig von bisherigen Denkweisen entstehen, sondern sogar teilweise mit ihnen konkurrieren.
Keywords: 650